Efektivitas Penggunaan Google Scholar dalam Menunjang Proses Penulisan Skripsi Mahasiswa Perpustakaan dan Ilmu Informasi - Aprilia, Siti Sofyah; Marlini, Marlini (YASIN, 2025)
The advancement of information technology has broadened access to scientific literature; however, its optimal utilization by students in thesis writing remains a concern. This study aims to evaluate the effectiveness of using Google Scholar in supporting the thesis writing process among 2021 cohort students of the Library and Information Science Program at Universitas Negeri Padang. A quantitative method with a descriptive approach was employed. Data were collected through a questionnaire distributed to 74 respondents selected via simple random sampling. The research instrument was developed based on two key indicators from the Technology Acceptance Model (TAM), namely Perceived Usefulness and Perceived Ease of Use, and analyzed using descriptive statistics. The results indicate that Google Scholar is perceived as highly useful (mean score 3.29) and easy to use (mean score 3.25), both falling within the "very good" category. These findings suggest that Google Scholar is effective in expediting information retrieval, enhancing academic productivity, and supporting the efficiency of thesis writing. In conclusion, the platform is well accepted by students and contributes positively to strengthening information literacy. Intensive training on the use of digital reference sources is recommended to optimize its function as a research support tool.